Honey physicochemical properties of three species of the brazilian Melipona - Lage, Lorena G.A.; Coelho, Lívia L.; Resende, Helder C.; Tavares, Mara G.; Campos, Lucio A.O.; Fernandes-Salomão, Tânia M. (Anais da Academia Brasileira de Ciências, 2011)
Physicochemical analyses were carried out to evaluate 27 samples of honeys from three species of the Brazilian genus Melipona (M. capixaba, M. rufiventris and M. mondury) from Espírito Santo and Minas Gerais States. The parameters water activity (Aw), percentage of soluble solids (Brix %), pH, acidity (meq/Kg) and moisture (%) were evaluated. The honey characteristics obtained from these samples were very similar to the ones from other Melipona species. However, regarding the honey from Apis (honey bee), only the pH values were similar. The low pH value and the high acidity detected in Melipona honey are potential factors for increasing the honey shelf life because they do not provide favorable conditions for the microbial development. On the other hand, the high level of water activity favors the growth of microorganisms, especially yeast, which demands a more careful handled and storage. The observed differences between Melipona and Apis honey reinforce the need for specific quality settings for stingless bee honey.

Análises fisico-quimicas foram realizadas para avaliar vinte e sete amostras de mel de três espécies do gênero Melipona (M. capixaba, M. rufiventris e M. mondury) coletadas nos Estados do Espírito Santo e de Minas Gerais. Os parâmetros atividade de água (aW), porcentagem de sólidos solúveis (Brix %), pH, acidez (meq.Kg-1) e umidade (%) foram avaliados. As características do mel dessas amostras foram muito similares às do mel de outras espécies de Melipona. Entretanto, para o mel de Apis apenas os valores de pH foram similares. O baixo valor de pH e a elevada acidez detectados no mel de Melipona são fatores potenciais para uma maior vida útil do mesmo por não oferecerem condições favoráveis ao desenvolvimento microbiano. Por outro lado, o alto teor de atividade de água favorece o crescimento de microrganismos, especialmente de leveduras o que requer maior cuidado no manuseio e armazenamento do mel. As diferenças observadas entre o mel de Melipona e o de Apis reforçam a necessidade de estabelecimento de padrões de qualidade específicos para o mel de abelhas sem ferrão.
Keywords: Honey; Melipona; Meliponini; Physicochemical data